1993
DOI: 10.1080/15287399309531802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vivo exposure to iodine‐131 on the frequency and persistence of micronuclei in human lymphocytes

Abstract: The validity of the micronucleus test as a biomarker of chromosome damage in dividing mammalian cells is well established. This assay was used to study the response of peripheral lymphocytes of a 34-yr-old male patient following treatment with 131I ablative radiation therapy following a total thyroidectomy. Coincidentally, 8 mo before diagnosis, the patient had provided a blood sample for an in vitro study of micronucleus induction following exposure to graded doses of x-rays. The background frequency in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 14 publications
2
15
0
1
Order By: Relevance
“…This possibility is supported by the genotoxicity associated with radiations which were observed by several studies. Such studies have investigated the level of genome damage and micronucleus in thyroid cancer patients environmentally exposed to radiation after the Chernobyl fallout (Sbrana et al 2006; Tronko et al 2007; Cardis and Hatch 2011), after Fukushema in Japan (Medalia 2011), in patients affected by thyroid cancer who underwent radiotherapy (Livingston et al 1993; Gutierrez et al 1997, 1999; Dardano et al 2007; Hooman et al 2008), and in people affected by thyroid nodules following occupational exposure to ionizing radiation (Brooks et al 2007; Scarpato et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…This possibility is supported by the genotoxicity associated with radiations which were observed by several studies. Such studies have investigated the level of genome damage and micronucleus in thyroid cancer patients environmentally exposed to radiation after the Chernobyl fallout (Sbrana et al 2006; Tronko et al 2007; Cardis and Hatch 2011), after Fukushema in Japan (Medalia 2011), in patients affected by thyroid cancer who underwent radiotherapy (Livingston et al 1993; Gutierrez et al 1997, 1999; Dardano et al 2007; Hooman et al 2008), and in people affected by thyroid nodules following occupational exposure to ionizing radiation (Brooks et al 2007; Scarpato et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The dose-independent increases of MN frequency in PBLs of DTC patients treated with 131-I were reported by Gutierrez et al (1999), Monsieurs et al (2000), and Joseph et al (2009), while Ballardin et al (2002) showed a dose-dependent effect of 131-I on MN frequency. Previous studies show an increased DNA damage in the PBLs of DTC patients treated with 131-I (Livingston et al 1993;Watanabe et al 1998;Ballardin et al 2002;Hooman et al 2008). However, our study is the first to examine whether the frequency of MN in the PBLs of radioiodine-treated DTC patients depends on the retention of radioiodine in the selected parts, as well as in whole patient's body after the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The blood is irradiated by β-particles emitted from circulating 131-I and from penetrating γ-radiation, originating from the activity dispersed throughout the body (Lassmann et al 2010). In PBLs of 131-I-treated patients chromosomal aberrations (BaugnetMahieu et al 1994;Gundy et al 1996;Monteiro et al 2000;Puerto et al 2000), the MN frequency (Livingston et al 1993;Watanabe et al 1998;Ballardin et al 2002;Lee et al 2002;Hooman et al 2008) and the CBPI (Gutirrez et al 1995;Ramirez et al 1997) were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented microphotographs were obtained by us in 1994 from the archive of hematological samples taken from the liquidators of Chernobyl disaster [23]. Livingston et al [24] demonstrated that the relationship between the frequency of detection of micronuclei and the radiation dosage is described by a non-threshold linear function: y= 2.78x + 3.71. This formed the basis for the widespread micronucleus test [17,25], validated in ionizing radiation biodosimetry.…”
Section: Nuclear Anomalies Of Human Lymphocytes Micronucleimentioning
confidence: 99%